Skema Gamifikasi berbasis Kontrak Cerdas untuk Perguruan Tinggi di Pendidikan Tinggi - Honesti, Leli; Aini, Qurotul; Setiawan, M Ikhsan; Puji Lestari Santoso, Nuke; Prihastiwi, Wahyu Yustika (APTISI Transactions on Management (ATM), 2022)
The Financial Scheme that plays an important role in helping students is the Gamification Scholarship Scheme. The Gamification scholarship scheme helps human life in the world of education. Gamification is an approach that uses elements in games or video games with the aim of motivating students in the learning process and maximizing feelings of enjoyment and engagement in the learning process. To encourage higher education, the government has done various things. However, there are several things that make it difficult for students to use it, such as distributing scholarships to students belonging to underprivileged families. The Gamification scholarship scheme is one of the most financially instrumental schemes in helping students, but it has not been verified which results in a lack of transparency between students and their respective Education Offices, then there is still a lack of tracking of application forms in this study, we propose a Smart Contract which addresses the lack of Scheme Scholarships for Colleges and Universities outlined above. It has four entities: Board of Education, Students, College and Bank. This Blockchain based smart contract has been developed to provide a user-friendly and transparent and constant environment between students and the education board. Blockchain platform has developed many applications but none can overcome the government scholarship scheme.